2019
DOI: 10.3390/genes11010011
|View full text |Cite
|
Sign up to set email alerts
|

Transferability and Polymorphism of SSR Markers Located in Flavonoid Pathway Genes in Fragaria and Rubus Species

Abstract: Strawberry (Fragaria) and raspberry (Rubus) are very popular crops, and improving their nutritional quality and disease resistance are important tasks in their breeding programs that are becoming increasingly based on use of functional DNA markers. We identified 118 microsatellite (simple sequence repeat-SSR) loci in the nucleotide sequences of flavonoid biosynthesis and pathogenesis-related genes and developed 24 SSR markers representing some of these structural and regulatory genes. These markers were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 79 publications
2
12
1
1
Order By: Relevance
“…The polymorphic neutral loci contain long dinucleotide sequences. Similar studies have confirmed that it is the motif homogeneity and the repeat frequency that are directly related to the number of alleles and the degree of heterozygosity compared with more heterogeneous and less frequently repeated motifs [34,51,54]. Such motifs were more typical of introns.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The polymorphic neutral loci contain long dinucleotide sequences. Similar studies have confirmed that it is the motif homogeneity and the repeat frequency that are directly related to the number of alleles and the degree of heterozygosity compared with more heterogeneous and less frequently repeated motifs [34,51,54]. Such motifs were more typical of introns.…”
Section: Discussionsupporting
confidence: 53%
“…The high variability of the DFR gene was also confirmed by SSR analysis data for different raspberry cultivars. Developed for the DFR genes, two markers from Rubus hybrid cultivar and one marker from the closely related Fragaria × ananassa did not work on the studied raspberry and blackberry cultivars [51].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic differences between Eurasian and American samples were identified, although they did not differ significantly in morphology. A set of 24 SSR loci, based on sequences of genes involved in regulation of biosynthesis and plant–pathogen interactions in Fragaria , were successfully applied to both Fragaria and Rubus germplasm (including rare cultivars and wild relatives) thus ensuring transferability of markers across genera [ 72 ].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Another particular approach was reported for two popular fruit crops such as strawberry ( Fragaria × ananassa Duchesne) and raspberry ( Rubus idaeus L.). Here, Lebedev et al (2020) [ 11 ] reported the potential transferability between the species of a large SSR panel for their employment in breeding programs assisted by functional DNA markers [ 11 ]. One hundred eighteen (118) microsatellite loci in the flavonoid biosynthesis were developed to assess the genetic diversity of 48 Fragaria and Rubus accessions, including wild species and rare cultivars, which differ in berry color, ploidy, and origin.…”
mentioning
confidence: 99%
“…One hundred eighteen (118) microsatellite loci in the flavonoid biosynthesis were developed to assess the genetic diversity of 48 Fragaria and Rubus accessions, including wild species and rare cultivars, which differ in berry color, ploidy, and origin. SSR panel may be a useful molecular tool in strawberry and raspberry breeding programs for improvement anthocyanin related traits [ 11 ].…”
mentioning
confidence: 99%